Simulation validation of flat-bed drying of paddy - Mohd Zin, Nur Fatin Awanis; Ibrahim, Mohd Nordin (Faculty of Engineering, Universiti Putra Malaysia, 2016)
A computer simulation program has been developed to predict the drying kinetics of paddy in flat-bed dryer (FBD) and it was found that the simulated results compared quite well with experimental results. In this current study, the simulation program is used to further validate the applicability by applying new set of input data comprising of different airflow rate and temperature; it is expected to have similar result as in previous study. This simulation program is also used to simulate the drying process by inclined-bed dryer (IBD); the simulated and experimental results are compared to evaluate whether the simulation developed specifically for FBD is also applicable for IBD. Experimentally, paddy dried with IBD showed a slightly shorter drying time compared to FBD. This simulation program which was developed specifically for FBD is expected to be applicable to IBD also. For FBD at low temperature, respective drying time for experiment and simulation were 19 hr and 19.5 hr, whilst 12 hr and 11.35 hr at high temperature. For IBD, experimental and simulated drying time at normal initial moisture content (MCi) showed less difference, whereas at high MCi, the simulated drying time was shorter than experimental. At high temperature, there was lesser difference between FBD and IBD drying curves for both experimental and simulation, whereas slight difference was observed at low temperature.